Parental weight status and early adolescence body weight in association with socioeconomic factors - Venetia Notara; Emmanuella Magriplis; Christos Prapas; George Antonogeorgos; Andrea Paola Rojas-Gil; Ekaterina N Kornilaki; Areti Lagiou; Demosthenes B Panagiotakos (Wolters Kluwer Medknow Publications, 2019)
BACKGROUND: Childhood obesity remains a major health issue. The understanding of the multifactorial nature of childhood obesity remains the cornerstone to eliminate the rising trends. This study aimed to examine the association between parental and childhood weight status, in relation to various socioeconomic (SE) factors. METHODS: A cross-sectional survey was conducted including 1190 children aged 10-12 years and their parents, during school years 2014-2016. Primary schools from five Greek counties (including Athens metropolitan area) were randomly selected. Parental and child data were collected through self-administered, anonymous questionnaires. Children's weight status was based on gender- and age-specific tables derived from the International Obesity Task Force body mass index (BMI) cut offs. General Linear Model (GLM), Univariate and multivariate analyses were applied. Multiple logistic regressions was used to determine the association between children and parents' weight status. RESULTS: Childhood prevalence of overweight and obesity was 25.9% (21.8% overweight and 4.1% obese), with prevalence being significantly higher in males (31.7% compared to 21.3%; P for gender differences < 0.001). The percent of overweight and obese male (34.4% and 43.1%) and female children (20.3% and 31.8%) significantly increased with paternal overweight and obesity status, respectively. The same relationship was observed between male children and maternal overweight and obesity status (43.4% and 65.7%). This was not evident among females (27% and 23.2%). Regression analysis showed a significant positive association with parental BMI, a negative association with both parental educational levels (low to high), living space, and parental age (P < 0.05, for all). Children's likelihood of being overweight or obese increased significantly with increasing parental weight status (P < 0.001). CONCLUSIONS: Parental weight status remained the most significant predictive factor for early adolescence obesity among various SE factors. Health promotion strategies should consider parental education as an effective childhood obesity preventive measure.